WORDMEANING. DIFFERENT APPROACHES TO MEANING. ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
The definition of the word meaning presents no less difficulty than the definition of the word itself. The word meaning renders the emotion or the concept in the mind of the speaker which he wants to convey to the listener in the process of communication. By concept we understand any discrete unit of human cognition. The word being a unit of language enters a number of combinations with other units stands in functional relations to other linguistic signs. Thus the meaning of the word not only fixes concepts by way of generalizing and reflecting reality, but it is realized on contexts and combinations. The meaning of the word is not homogeneous. It is closely connected with the object it names and the concept it fixes. It is also connected with the sound form besides it is realized in different relations with other concepts. There are two main approaches to word meaning: 1. relative approach, according to which each linguistic sign (word) gets its meaning only in some semantic field or paradigmatic relations. 2. the referential or denotational approach, according to which the meaning of the word is autonomous, it’s an integral part of the word, though is realized in contexts and this approach is shown as a triangle (symbol – the word, concept – thought; referent – object, denoted by the word).